2004
DOI: 10.1191/0969733004ne693oa
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study on the Development of Moral Judgement in Korean Nursing Students

Abstract: This longitudinal study examined the development of moral judgement in 37 nursin students attending a university in Suwon, Korea. The participants completed the Korean version of the Defining Issues Test to allow analysis of their level of moral judgement. The development of moral judgement was quantified using 'the moral development score' at each stage (i.e. the six stages detailed by Kohlberg) and the 'P(%) score' (a measure of the overall moral judgement level). The results were as follows: (1) the moral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…It is a stage or station at which there is the fullest possible integration of professional identity and the greatest enhancement of moral competencies and is arrived at when students are in their final year of study. [1][2][3]6,[10][11][12]27,28 To reach this level, the students need to have ''bonded'' with nursing. In a study of Japanese nursing students, ''bonding into nursing'' was defined as the process by which each nurse fully established her or his professional identity as a nurse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a stage or station at which there is the fullest possible integration of professional identity and the greatest enhancement of moral competencies and is arrived at when students are in their final year of study. [1][2][3]6,[10][11][12]27,28 To reach this level, the students need to have ''bonded'' with nursing. In a study of Japanese nursing students, ''bonding into nursing'' was defined as the process by which each nurse fully established her or his professional identity as a nurse.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, the results of two studies on Korean nursing students showed that the level of moral development was higher at graduation. 12,13 There is thus a plethora of studies that indicate that nursing education has a positive effect on moral development of nursing students during college years, culminating in a high level of moral development at graduation. However, the influential factors within nursing education that students are exposed to and how this relates to an unfolding evolvement of higher moral development have not been specifically identified.…”
Section: Moral Development Within Nursing Studentsmentioning
confidence: 98%
“…The development of students' moral judgment also varies according to their academic years. Kim et al 6 found that moral development scores were higher in fourth year than in first year students. Lemonidou et al 29 …”
Section: Introductionmentioning
confidence: 98%
“…Ethics education should begin early in the educational process, include case studies using problem‐solving approaches, and involve mentorship in the clinical practice experiences (Doherty 2005). Learning environments that ‘provide opportunities for group participation, shared decision‐making, and assumption of responsibility for the consequences of actions tend to stimulate the development of higher levels of moral judgement’ (Kim et al . 2004, p. 255).…”
Section: Introduction and Purposementioning
confidence: 99%